Pemikiran Muhammad Quraish Shihab Tentang Nikah Siri - Muhammad Abdul Basir; Nurul Ainun Azisah; Elisa Rani; Muh Fasral Hafid; Nurhikma; Muhammad Fatur Anggara; Eko Nursalim (STIT Syekh Muhammad Nafis Tabalong, 2022)
<p style=